ON THE ISSUE OF THE SUSTAINABLE DEVELOPMENT OF CITY PARKS - Svasheko, Anton; Prokopenko, Nataliia (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
The relevance of this theoretical study stems from the need to ensure the sustainable development of cities and to improve their spatial structure, taking into account factors such as recreational use of natural resources, socio-economic development and contemporary environmental requirements. Intensive urbanisation processes pose new challenges for the harmonious functioning of urban parks, which must meet the health and recreational needs of the population, promote the inclusive development of the urban environment, and ensure the conservation of natural resources and ecological balance.Research into the issue of sustainable development of urban parks is driven by the objective growth in the importance of the ecosystem services they provide to society, particularly in terms of improving the quality of life of the population, maintaining environmental safety and ensuring the socio-economic well-being of local communities. At the same time, the need to effectively meet the health, cultural and recreational needs of city dwellers is becoming particularly pressing in the context of increasing anthropogenic pressure on urbanised areas.